2013
DOI: 10.1080/10286020.2013.790377
|View full text |Cite
|
Sign up to set email alerts
|

Five new flavonoid glycosides fromNervilia fordii

Abstract: Five new flavonoid glycosides, namely nervilifordins F-J (1-5), were isolated from the 60% EtOH extract of the aerial parts of Nervilia fordii, along with three first isolated flavonoids (7, 8, and 13) and five known flavonoids (6, 9-12). The structures of new compounds were elucidated on the basis of 1D and 2D NMR and MS studies. Their anti-inflammatory activities were tested by measuring their inhibitory effects on nitric oxide production in lipopolysaccharide-activated RAW264.7 macrophages. Compounds 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…It is frequently used for the therapy of various diseases, such as bronchitis, stomatitis, acute pneumonia, and laryngitis. [1][2][3][4][5] Phytochemical studies on genus Nervilia have led to the identification of about 58 compounds, including 24 flavonoids, 10 terpenes, and some sterols and amino acids. [3] Our previous study on this plant led to the isolation of several flavonols from the ethyl acetate extract.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is frequently used for the therapy of various diseases, such as bronchitis, stomatitis, acute pneumonia, and laryngitis. [1][2][3][4][5] Phytochemical studies on genus Nervilia have led to the identification of about 58 compounds, including 24 flavonoids, 10 terpenes, and some sterols and amino acids. [3] Our previous study on this plant led to the isolation of several flavonols from the ethyl acetate extract.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Phytochemical studies on genus Nervilia have led to the identification of about 58 compounds, including 24 flavonoids, 10 terpenes, and some sterols and amino acids. [3] Our previous study on this plant led to the isolation of several flavonols from the ethyl acetate extract. [6] The present research reports the isolation and structure elucidation of four flavonol compounds (1)(2)(3)(4) from the remaining fractions of the ethyl acetate extract (figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During SARS epidemic period, it showed that the decoctions of traditional Chinese herbs could significantly alleviate SARS symptoms in clinic [3,4,[6][7][8]. Thus, we have been studying the phytochemicals and pharmacological activities of Nervilia fordii since 2009 [9][10][11][12][13]. Modern pharmacological studies demonstrated that Nervilia fordii has antitumor, antiviral, analgesic, and anti-inflammatory activities [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies demonstrated that Nervilia fordii has antitumor, antiviral, analgesic, and anti-inflammatory activities [14][15][16][17]. In our previous work, we found that the flavonoids and polysaccharides are two main constituents in Nervilia fordii which display compelling anti-inflammatory activities [10,11,13].…”
Section: Introductionmentioning
confidence: 99%